Evaluation of validity and limitations of the soybean canopy height‐to‐row spacing ratio as an onsite index to control weeds using diverse soybean accessions. Issue 3 (29th August 2019) - Kurokawa, Shunji; Kaga, Akito; Tsuda, Mai; Sekine, Daisuke; Shibuya, Tomoko
Abstract : A canopy height‐to‐row spacing ratio (CHRSR) of 1.0 is expected to be a simple and practical onsite index for soybean growers to determine when further weed control is no longer necessary. This is decided when relative photosynthetic photon flux density (PPFD) reaches 50% under the soybean canopy. To evaluate the validity of this index, a 2‐year field experiment was conducted to compare days after sowing (DAS) to reach a relative PPFD of 50% (defined as PPFD50) and DAS to reach a CHRSR of 1.0 (defined as CHRSR1.0) in 190 accessions with different canopy architectures from a soybean core collection. A total of 104 accessions, for which final relative PPFD reached <10% in 2014, were examined for the differences between CHRSR1.0 and PPFD50. The mean and median values of the difference in 2014 were 0.02 and 2.2, respectively. Similarly, the mean and median values in 2015 were 2.8 and 2.6, respectively. Thus, CHRSR1.0 tended to be achieved slightly later than PPFD50, so a consideration was made that there would be a negligible risk of failure if growers used CHRSR1.0 to determine the termination time for weed control in the most of accessions. Although there were some accessions with a standing type of morphological characteristics or with a smaller or narrower leaf, showing negative differences between CHRSR1.0 and PPFD50 larger than 1 week, a CHRSR of 1.0 could be used to estimate PPFD50 in most of accessions without risk of failure to control weeds.